2009
DOI: 10.1007/s11556-009-0051-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and physical activity level on functional fitness in older adults

Abstract: It is difficult to distinguish between the effects of age and physical activity level in the functional fitness level of older adults. The objective of this study was to determine the effects of age and physical activity level on some functional fitness parameters in community-dwelling older adults.Two hundred twenty-nine elderly (111 female; 118 male) aged between 65-87 years living in the Balçova municipality region were divided into two groups: the young elderly (65-69 years old) and the elderly (70 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 17 publications
(24 reference statements)
1
21
0
Order By: Relevance
“…The decline in all the fitness variables was expected, as ageing is a natural and inevitable process with several previous studies reporting a decrease of fitness with age [24,25]. Similarly to previous studies [26], we found that this decline was not linear, as both males and females in the oldest group (≥75 years) showed the largest decreases for agility, walking speed and endurance capacity.…”
Section: Discussionsupporting
confidence: 86%
“…The decline in all the fitness variables was expected, as ageing is a natural and inevitable process with several previous studies reporting a decrease of fitness with age [24,25]. Similarly to previous studies [26], we found that this decline was not linear, as both males and females in the oldest group (≥75 years) showed the largest decreases for agility, walking speed and endurance capacity.…”
Section: Discussionsupporting
confidence: 86%
“…Aging is a process characterized by declining of the physical and health function observed over time. (Tuna, Edeer, Malkoc, & Aksakoglu, 2009) This decline is a consequence of reduction in muscle strength, balance, endurance, agility, flexibility and increase in comorbidities related to the aging process. (Cruz-Jentoft et al, 2010;Glass, de Leon, Marottoli, & Berkman, 1999) Physical and health condition are associated with social support and social participation, which are protective factors to functionality and health in older people.…”
Section: Introductionmentioning
confidence: 99%
“…Delimiting the concept of fitness to the elderly, we deem it more appropriate to use the term functional capacity, understood as the ability to efficiently carry out basic activities of daily living that people should do to take care of themselves and live independently and autonomously 19 …”
Section: Introductionmentioning
confidence: 99%